Reliable Mass Spectrometry Based Method For Quantitative Analysis Of Tecovirimat - Banothu Bhadru,; V.Venkata Rao,; Suryadevara Vidyadhara, (International Journal of Pharma and Bio Sciences, 2020)
Tecovirimat prevents viral egression from the cell by inhibiting protein P37 or its ortholog in orthopox viruses. This results in blocking viral dissemination in hosts. A simple, specific, sensitive LC/MS/MS method for the quantization of Tecovirimat in spiked plasma with Penciclovir as an internal standard by using UPLC-ESI-MS/MS. The chromatographic separation was achieved with 10 mM Ammonium acetate buffer (pH 4.0): Methanol: Acetonitrile (20:40:40% v/v/v) using the CORTECS C18, 90 Å, 2.7 µm, 4.6 mm X 150 mm analytical column. The total analysis time was 4.0 min and flow rate was set to 0.5 ml/min. The mass transitions of Tecovirimat and Penciclovir obtained were m/z 377.1/188.1 and 254.1/152.1. The method was fully validated for its sensitivity, selectivity, accuracy and precision, matrix effect, recovery, and stability. The curve indicates correlation coefficient (r2) was superior than 0.998 with linear range of 0.03-48.0 n.g/m.L. The intra- and inter-day precision and relative error were all within 10 %. Despite achieving high mean recovery (>80 %), no interference peaks or matrix effects were observed. An accurate and reproducible novel bio-analytical method was fabricated for estimation of Tecovirimat in plasma samples by UPLC-ESI-MS/MS will be used for regular analysis and appropriate for therapeutic drug monitoring. The method permits laboratory scientists with access to the appropriate instrumentation to perform rapid Tecovirimat determination.